THE SPECTRUM OF INTRADURAL SPINAL TUMORS - Ali, Mumtaz; Khan, Zahid; Sharafat, Seema; Mehmood, Khalid; ., Alamgir; Khan, Pervaiz; Usman, Mohammad (Journal of Postgraduate Medical Institute, 2011)
Objective: To assess the spectrum of clinical, radiological and histological features of patients with intradural spinal tumors. Materials and methods: This descriptive study was carried out in Department of Neurosurgery Lady Reading Hospital Peshawar, from April 2003 to March 2009. Medical records of patients with spinal tumors were revieqwed and patients operated for intradural spinal tumors were identified. A total of 312 patients, out of 525 cases of spinal tumors, with different intradural spinal tumors were considered in this study. Their clinical features, radiological reports, peroperative findings and histological reports were analyzed in different aspects. Results: There were total of 312 patients with age range from 2 years to 74 years, with median age of 38 years. Out of these 187 were males and 125 were female, overall male to female ratio of 1.5:1. Backache, leg weakness, parasthesia and poor sphincters were the main clinical features. MRI spine (274 cases) was the main diagnostic tool along with plain X-rays and X-ray myelography in limited cases (35 cases). CT myelogram was done only in 3 cases. The common site of involvement was dorsal spine followed by lumber and cervical spines respectively in 185, 80 and 47 cases. Histological report was suggestive of Neurofibroma in 166, Meningioma in 96, Ependymoma in 20, Dermoid in 12, Astrocytoma in 7, Hemangioblastom and Tuberculoma in 3 cases each and Hydatid cyst in one case. Conclusion: Neurofibroma and meningioma constituted majority of cases belonging to intradural extramedulary group, while ependymoma and astrocytoma were common intramedullary tumors. Third and 5th decade of life was the common age group for both Intramedulary and extramedulary tumors. Intramedulary lesions were common in 3rd decade of life.